(untitled) (Annals of Medical Research, 2022)
Aim: This study aimed to investigate to usability of ischemia modified albumin (IMA) and IMA/albumin ratio (IMAR) values in the follow-up of ALF patients. King College criteria (KCC) and Model for End-Stage Liver Disease (MELD) score are the most commonly used criteria in the follow-up of patients with acute liver failure (ALF). However, these criteria cannot always predict prognosis and the need for liver transplantation (LT). Materials and Methods: IMA and IMAR values of 23 ALF patients and 43 healthy volunteers were measured. Then IMA and IMAR values were compared with KCC and MELD score to predict LT requirement and prognosis in ALF patients. Results: IMA and IMAR values were significantly higher in ALF patients compared healthy volunteers (p=0.001, p=0.001; respectively). IMA and IMAR values predicted LT requirement in ALF patients such as KCC and MELD (≥30) score (p=0.006, p=0.04, p=0.001, p=0.03; respectively). IMA values were found to better than KCC in predicting mortality (p=0.008, p=0.02; respectively). MELD (≥30) score failed to predict mortality (p=0.44). Conclusion: IMA and IMAR values can be used as diagnostic biomarkers in ALF patients. IMA is a better prognostic biomarker in the follow-up of ALF patients.